Flooding risk of cropland areas by repiquetes in the western Amazon basin: A case study of Peruvian Tamshiyacu City - Valenzuela, Jonathan (2023)
Study región: The western Amazon basin at Tamshiyacu gauging station (near the Iquitos City) hosts floodplain agriculture that can be affected by the sudden reversal in direction of water levels known as “repiquetes” that produce intermittent flooding. Study focus: This study assesses repiquete flooding risk in riparian crop areas based on statistical analyses of repiquete events registered from 1996 to 2018, hydraulic modeling to estimate flooded extension, and assessment of climatological characteristics during the formation of repiquetes. New hydrological insights: Floods (≥ 20 cm) produced by repiquetes in riparian crop areas between 83.00 and 88.00 m above sea level (masl) occur 1.8 times per year. However, not all elevation ranges have the same flooding risk to crops. Terrain elevations between 85.31 and 87.00 masl have a reduced flooding risk of 0.35 per year. Likewise, areas with elevations between 87.00 and 88.00 masl (43% of the total area) were not affected by repiquetes. Extreme repiquetes (study cases of 2002 and 2008) have been influenced by the increase of atmospheric moisture flux convergence and precipitation over both the northern Ucayali and Marañón basins through the six previous days. Flood impacts from the extreme event of 2002 (2008) could have reached 40% (25%) of the available area for agriculture at the initiation of the repiquete.